KONSEP DASAR ILMU AKHLAK DAN IMPLEMENTASINYA DALAM KEHIDUPAN - Devi Abdiyatuzzahro; Siti Fitriyah Handayani; Maftuh Ajmain (Adisam Publisher, 2025)
Ethics is a branch of knowledge that discusses moral values and ethics that serve as guidelines in human life. The basic concept of ethics encompasses an understanding of good and bad, as well as how humans should behave in various aspects of life. The importance of ethics in life lies in its role in shaping a noble personality, creating harmonious social relationship, and building a civilized society. Ethics not only focuses on individual aspects but also has implications for social, cultural, and even political life. The urgency of ethics is increasingly important in the modern era, which is marked by various moral challenges such as ethical crises, moral decadence, and the influence of globalization that can erode local values. Threfore, undersanding and applying ethics becomes an essential need in building a better and civilized life.